Anti-Tubercular Treatment of Tuberculous Meningitis Cause Paradoxical Multiple Neurotuberculoma - Kumar, MK; Kumar, P; Singh, A (Journal of Nepal Paediatric Society, 2015)
Tuberculosis is the most common cause of infectious disease related mortality worldwide. Paradoxical reactions to antituberculous treatment have created difficulties in the management of extrapulmonary tuberculosis, particularly central nervous system tuberculosis. We report a three years baby with tuberculous meningitis, who was treated outside with anti-tuberculous drugs without steroid one month back and presented in our emergency as status epilepticus. This case emphasizes the importance of addition of steroid along with anti-tubercular drugs in the treatment of central nervous system tuberculosis. J Nepal Paediatr Soc 2014;34(3):236-238 DOI: http://dx.doi.org/10.3126/jnps.v34i3.10752